Synthesis of Phthalyl Substituted Imidazolones and Schiff Bases as Antimicrobial Agents - Pramilla Sah; Neha Saraswat; Manu Manu (E-Journal of Chemistry)
A new series of phthalyl substituted imidazolones (4a–g) and Schiff bases (5a–d) were synthesized from 2-methyl-(m-nitro-1,3-dioxo-1,3-dihydro-(2H)-isoindole-2-yl)-5-amino-1,3,4-thiadiazole (3a–b). Compounds (3a–b) were prepared by cyclisation of 2-(m-nitro-1,3-dioxo-1,3-dihydro-(2H)-isoindole-2-yl)methyl ethanoate (2) with thiosemicarbazide. 2-(m-nitro-1,3-dioxo-1,3-dihydro-(2H)-isoindole-2-yl)ethanoic acid (1) in presence of thionyl chloride and methanol gave the ester (2) while compound (1) was synthesized by aminolysis of phthalic anhydride with glycine. The compounds were characterized by spectral techniques of IR, 1H NMR, Mass and elemental analysis. All the synthesized compounds (4a–g) and (5a–d) were screened for their antibacterial activity against the pathogenic strains E. coli, P. aureus, C. freundii while antifungal activity was evaluated against A. niger, A. flavus, Penicillium sp. and C. albicans.